Role of membrane lipids and plasma lipoproteins in the regulation of activated protein C function - Johnson, Jennifer (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Haematology, 2013)
Activated protein C (APC) is an important anticoagulant factor that serves to downregulate thrombin generation. APC also has several cytoprotective properties, including anti-apoptotic and endothelial barrier stabilizing signalling. This study aimed to investigate the role of lipids in mediating the APC pathway.
Keywords: Haematology, M.D.; Ph.D. Trinity College Dublin